Supporting teachers in orchestrating CSCL classrooms - Dimitriadis, Yannis A. (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
Teachers face numerous problems in orchestrating technology-enhanced classrooms, especially when dealing with complex pedagogies such as collaborative learning. Designing and putting in practice computer-supported collaborative learning (CSCL) lesson plans requires an extensive knowledge both in pedagogy and technology, which needs to match teachers’ beliefs and goals. This paper and keynote talk addresses teacher practices as well as the support that may be provided in order to achieve the goals of effective and sustainable creation and use of CSCL lesson plans or scripts. Some illustrating examples are drawn from the GSIC/EMIC research work in the past decade, as well as other initiatives in the quest for appropriate mediating artefacts that may support the complex life cycle of CSCL scripts.